Tibial anterior compartment compressibility in healthy subject, measured using compression sonography - Anwander, Helen; Büchel, Livia; Krause, Fabian; Siebenrock, Klaus; Schmid, Timo (Injury, 2022)
•Mean compartment compressibility ratio R10–80 of the tibial anterior compartment in healthy subjects was 15.9 ± 3.6%.•Compartment compressibility did not depend on demographic parameters or sport activity.•Application of 10mbar instead of 0mbar for the low-pressure measurement increased image quality and subsequently the quality of the measured values.•Compression sonography is reliable with very high intra- and interobserver correlation. Compression sonography has been introduced for non-invasive measurement of compartment compressibility and possible diagnostic tool for acute or chronic compartment syndrome in studies using human cadavers and animal models. To date, standard values in healthy subjects are not yet defined. The aim was to define standard compartment compressibility values in healthy human subjects and to assess the reliability of this measurement method. In 60 healthy volunteers, using ultrasound, the diameter of the tibial anterior compartment was measured while applying no pressure, 10mbar and 80mbar of external pressure. A pressure manometer on the ultrasound head was used to monitor the externally applied pressure. Compartment compressibility ratio (R0–80, respectively R10–80) was calculated as following: The delta of the compartment diameter with high and low external pressure, divided through the diameter with low external pressure. In 10 volunteers, two examinators conducted each two measurements to assess the reliability. Mean compartment compressibility ratio R10–80 was 15.9% ±3.6 (range: 7.2 – 22.2). Mean compartment compressibility ratio R0–80 was 18.2% ±5.0 (3.0 – 32.1). There was no significant correlation with lower leg circumference, height, weight, BMI, gender, hours of sport per week and type of sport (e.g. weightlifting/ cardio). For R10–80, intraobserver ICC 2.1 was 0.89 for an experienced observer and 0.79 for a non-experienced observer. Interobserver ICC 2.1 was 0.78. For R0–80, intraobserver ICC 2.1 was 0.71 for the experienced and 0.56 for the unexperienced observer. Interobserver ICC 2.1 was 0.59. In healthy volunteers between 18 and 50 years of age, mean compartment compressibility ratio R10–80 was 15.9% ±3.6, independent of demographic factors and sport activity. Application of 10mbar instead of 0mbar increased image quality. Subsequently, R10–80 showed lower standard deviation and both higher intraobserver and interobserver reliability than R0–80. Using R10–80, this measurement method is reliable with very high intra- and interobserver correlation.